General health status among teaching staff during COVID-19 pandemic - Kamarulzaman, Wirawani (Academia Industry Networks (002911676-U), 2022)
In conjunction with the covid-19 disease, the pandemic and lockdown have accelerated the shift from traditional to online educational methods, and relationships have been altered by avoiding direct contact with others, which has had an adverse effect on the mental health of teaching staff. Physical activity appeared to be beneficial in this bizarre situation, as it appeared to help prevent mental disorders such as anxiety and depression. The purpose of this study is to investigate the general mental health of teaching staff, as well as its relationships with service duration, work sector, and level of teaching, among other things. The health status of 220 members of the teaching staff was assessed using the General Health Questionnaire (GHQ-28) questionnaire. The findings revealed a statistically significant relationship between their health status and all three variables, demonstrating that the pandemic has caused stress among teaching staff with varying levels of service duration, work sector, and whether they are teaching at the primary, secondary, or tertiary levels. There are a few recommendations for future research included in this paper as well.